Are Hofstede's and Schwartz's values frameworks equally predictive across contexts? - Siew, Imm Ng; Lim, Xin Jean (Fundacao Escola de Comercio Alvares Penteado (F E C A P), 2019)
Purpose – This study uses bipolar cultural dimensions (i.e., Hofstede’s and Schwartz’s values frameworks) to predict trade between countries and consumption behaviour. Design/methodology/approach – The analysis in this paper was based on secondary data. Consequently, there were some missing data that limited the number of countries that could be examined in terms of trade and consumption aspects. Stepwise regressions were performed to test the hypotheses. Findings – This study found that egalitarian-hierarchical distance predicts trade negatively, providing support to the idea that cultural similarity drives trade. On top of that, the study suggested that consumption divergence is more likely than consumption convergence. Cultural values were significant predictors of consumption even when income was controlled, suggesting that consumers want to express their values systems through consumption when they have the financial means to do so. Originality/value – The empirical analysis illustrated that bipolar cultural dimensions of these frameworks predict trade and consumption behaviour differently, thus providing evidence on the applicability of the cultural frameworks in different contexts.